2018
DOI: 10.2217/fca-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

Has the Clinical Profile of Patients With Nonvalvular Atrial Fibrillation Treated With Rivaroxaban Changed in the Last 5 Years of use?

Abstract: Although, the initial prescription of rivaroxaban was mainly performed in very elderly patients and/or with a higher bleeding risk, this has been extended to the overall nonvalvular atrial fibrillation population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…ROCKET-AF was the clinical trial that included those patients with the highest thromboembolic risk among all DOAC trials 3941. When rivaroxaban was introduced in clinical practice, it was mainly prescribed in patients with a better clinical profile,1315 or among patients with a high bleeding risk 22. However, as our study has shown, the experience with rivaroxaban has increased in routine practice, it is prescribed in different clinical settings, and its use has been extended to the entire AF population, regardless of the clinical profile of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROCKET-AF was the clinical trial that included those patients with the highest thromboembolic risk among all DOAC trials 3941. When rivaroxaban was introduced in clinical practice, it was mainly prescribed in patients with a better clinical profile,1315 or among patients with a high bleeding risk 22. However, as our study has shown, the experience with rivaroxaban has increased in routine practice, it is prescribed in different clinical settings, and its use has been extended to the entire AF population, regardless of the clinical profile of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in routine practice may help determine in which patients DOACs are being prescribed, and whether they are being used properly. Although in recent years a number of studies on the use of rivaroxaban in clinical practice in Spain have been published, these studies have been limited to one single center or healthcare area or to a specific medical specialty 1622. In this context, it is important to analyze the clinical management of rivaroxaban not limited to a specific area or specialty in Spain.…”
Section: Introductionmentioning
confidence: 99%